Mitochondrial remodeling in mice with cardiomyocyte-specific lipid overload. (February 2015) - Elezaby, Aly; Sverdlov, Aaron L.; Tu, Vivian H.; Soni, Kanupriya; Luptak, Ivan; Qin, Fuzhong; Liesa, Marc; Shirihai, Orian S.; Rimer, Jamie; Schaffer, Jean E.; Wilson S., Colucci; Edward J., Miller
Abstract: Background: Obesity leads to metabolic heart disease (MHD) that is associated with a pathologic increase in myocardial fatty acid (FA) uptake and impairment of mitochondrial function. The mechanism of mitochondrial dysfunction in MHD, which results in oxidant production and decreased energetics, is poorly understood but may be related to excess FAs. Determining the effects of cardiac FA excess on mitochondria can be hindered by the systemic sequelae of obesity. Mice with cardiomyocyte-specific overexpression of the fatty acid transport protein FATP1 have increased cardiomyocyte FA uptake and develop MHD in the absence of systemic lipotoxicity, obesity or diabetes. We utilized this model to assess 1) the effect of cardiomyocyte lipid accumulation on mitochondrial structure and energetic function and 2) the role of lipid-driven transcriptional regulation, signaling, toxic metabolite accumulation, and mitochondrial oxidative stress in lipid-induced MHD. Methods: Cardiac lipid species, lipid-dependent signaling, and mitochondrial structure/function were examined from FATP1 mice. Cardiac structure and function were assessed in mice overexpressing both FATP1 and mitochondrial-targeted catalase. Results: FATP1 hearts exhibited a net increase (+ 12%) in diacylglycerol, with increases in several very long-chain diacylglycerol species (+ 160–212%, p  < 0.001) and no change in ceramide, sphingomyelin, or acylcarnitine content. This was associated with an increase in phosphorylation of PKCα and PKCδ, and a decrease in phosphorylation of AKT and expression of CREB, PGC1α, PPARα and the mitochondrial fusion genes MFN1, MFN2 and OPA1. FATP1 overexpression also led to marked decreases in mitochondrial size (− 49%, p  < 0.01), complex II-driven respiration (− 28.6%, p  < 0.05), activity of isolated complex II (− 62%, p  = 0.05), and expression of complex II subunit B (SDHB) (− 60% and − 31%, p  < 0.01) in the absence of change in ATP synthesis. Hydrogen peroxide production was not increased in FATP1 mitochondria, and cardiac hypertrophy and diastolic dysfunction were not attenuated by overexpression of catalase in mitochondria in FATP1 mice. Conclusions: Excessive delivery of FAs to the cardiac myocyte in the absence of systemic disorders leads to activation of lipid-driven signaling and remodeling of mitochondrial structure and function. Highlights: We examine if cardiomyocyte lipid excess leads to mitochondrial dysfunction. Lipid excess causes mitochondrial remodeling in FATP1 transgenic mice. FATP1 hearts have decreased mitochondrial size and respiration, unchanged ATP. ROS are not increased in FATP1 mitochondria.